Chipmakers ARM for Battle in Traditional Computing Market. - Ortiz Jr., Sixto (Computer (00189162), 2011)
Despite many significant challenges, ARM chip developers are pushing ahead with plans to go beyond mobile devices and enter the laptop, desktop, and server markets.